1999
DOI: 10.1108/01437739910302524
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between commitment and organizational culture, subculture, leadership style and job satisfaction in organizational change and development

Abstract: The concept of organizational commitment has been examined extensively in organizational literature, yet the relationships between organizational culture, subculture and commitment have received little attention so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
198
2
31

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(254 citation statements)
references
References 42 publications
23
198
2
31
Order By: Relevance
“…This result is also consistent with the findings by Khalili (2014), Abbasi et al (2014), Acar (2012), Altin Gulova and Demirsoy (2012), Ziaee et al, (2011Ziaee et al, ( ), İpek (2010, Manetje andMartins (2009), Okpara (2008), Silverthorne (2004), Ingersoll et al (2000, and Lok and Crawford (1999).…”
Section: Resultssupporting
confidence: 82%
“…This result is also consistent with the findings by Khalili (2014), Abbasi et al (2014), Acar (2012), Altin Gulova and Demirsoy (2012), Ziaee et al, (2011Ziaee et al, ( ), İpek (2010, Manetje andMartins (2009), Okpara (2008), Silverthorne (2004), Ingersoll et al (2000, and Lok and Crawford (1999).…”
Section: Resultssupporting
confidence: 82%
“…The finding of this study supports the hypothesis that organizational culture is linked to turnover intention; hence, turnover intention would be decreased if an employee demonstrates a positive attitude and put high value to the organizational culture. This finding is supported by past studies such as in, Booth and Hamer (2007), Lok and Crawford (1999), MacIntosh and Doherty (2010), Park and Kim (2009), Shim (2010), and Silverthorne (2004. All of these studies concluded that organizational culture is an integral variable in forecasting employee turnover intention.…”
Section: Leadership Behaviour Organizational Culture and Turnover Insupporting
confidence: 79%
“…Lok and Crawford, (1999);(2004) and confirmed that organizational culture was important organizational antecedents of job satisfaction and commitment. These results were supported by Zavyalova and Kucherov, (2010), and Zainol, (2009), who pointed out that organizational culture can influence the organizational commitment and organizational culture have a significant relationship with three dimensions of organizational commitment such as affective, continuance and normative.…”
Section: Meyer and Allen Model (1991)mentioning
confidence: 69%
“…Organizational commitment has been researched in various contexts; including (a) Perceived Organizational Support (O'Driscoll and Randall, 1999), (b) Performance Among Guest Workers (Shawa, et al 2003), (c) Job Outcomes (Wasti, 2005), (d) Trust, Innovative Behaviour (Lee, 2008), (e) Organizational Culture and Leadership Style (Lok and Crawford, 1999) and (f) Job Satisfaction (Lim, 2010 andShurbagi andZahari, 2013b). Some of these studies pointed out that organizational commitment have a positive relationship with these variables.…”
Section: Organizational Commitmentmentioning
confidence: 99%